Blood Pressure Pattern and Target Organ Damage in Patients With Chronic Kidney Disease. Issue 4 (October 2018) - Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Störk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Jürgen; Janka, Rolf; et al.
Abstract : In patients with chronic kidney disease, data on blood pressure (BP) pattern and its association with target organ damage, which indicates elevated cardiovascular risk, are sparse. In 305 treated hypertensive chronic kidney disease patients, we assessed BP pattern, left ventricular mass (magnetic resonance imaging), intima-media thickness (ultrasound), 24-hour–pulse wave velocity and 24-hour–central augmentation index (Mobil-O-Graph). Controlled hypertension (normal office and ambulatory BP) was found in 41% and sustained uncontrolled hypertension (elevated office and ambulatory BP) in 30% of patients. Misclassification of BP status occurred in 29%: white coat uncontrolled hypertension (elevated office but normal ambulatory BP) was detected in 11% and masked uncontrolled hypertension (normal office but elevated ambulatory BP) in 18% of patients. Left ventricular mass was increased in white coat uncontrolled hypertension (+11.2 g), masked uncontrolled hypertension (+9.4 g), and sustained uncontrolled hypertension (+16.6 g) compared with controlled hypertension. Intima-media thickness was similar across all 4 BP groups. Twenty-four hour–pulse wave velocity and 24-hour–central augmentation index were increased in masked uncontrolled hypertension (+0.5 m/sec and +2.5%) and sustained uncontrolled hypertension (+0.5 m/sec and +2.9%) compared with controlled hypertension. In conclusion, based on office BP measurements, misclassification of true BP status occurred in almost one-third of chronic kidney disease patients. Both types of misclassification (white coat uncontrolled hypertension and masked uncontrolled hypertension) were associated with parameters of target organ damage. Ambulatory BP monitoring should be used routinely to identify chronic kidney disease patients at high cardiovascular risk. Abstract : Supplemental Digital Content is available in the text.